Watershed modeling applications with a modular physically-based and spatially-distributed watershed educational toolbox. (June 2015) - Huning, Laurie S.; Margulis, Steven A.
Abstract: Introductory hydrology courses traditionally focus on process-based hydrology (i.e. precipitation, evaporation, runoff, etc.) that is ultimately unified through watershed modeling. Although physically-based and spatially-distributed hydrologic models are arguably valuable learning tools, they typically have steep learning curves and high computational costs. To overcome these common drawbacks in hydrology education, we developed the user-friendly, open-access Mo dular D istributed W atershed E ducational T oolbox (MOD-WET). MOD-WET is a compilation of highly modular functions designed for process-based applications, which are integrated into a physically-based and spatially-distributed watershed model. When students use the toolbox to study individual processes, they become familiar with the fundamental components forming the hydrologic model. Student feedback indicates that this approach makes a holistic understanding of the water cycle more accessible to students. Hydrograph sensitivity to watershed characteristics (size, slope, roughness, etc.) is demonstrated. The capability of MOD-WET to model warm and cold land processes is also illustrated for a snow-covered basin. Highlights: We present an educational physically-based, distributed watershed model (MOD-WET). Process-based hydrologic concepts can be studied with the modular toolbox functions. Hydrograph sensitivity to basin size, shape, slope, and roughness is illustrated. The performance of MOD-WET is demonstrated in snow-dominated watershed applications. MOD-WET makes a holistic comprehension of the water cycle accessible to students.